2017
DOI: 10.1021/acsami.7b01929
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Pool Boiling Heat Transfer Using Aligned Silicon Nanowire Arrays

Abstract: Enhancing the critical heat flux (CHF), which is the capacity of heat dissipation, is important to secure high stability in two-phase cooling systems. Coolant supply to a dry hot spot is a major mechanism to prevent surface burn-out for enhancing the CHF. Here, we demonstrate a more ready supply of coolant using aligned silicon nanowires (A-SiNWs), with a high aspect ratio (>10) compared to that of conventional random silicon nanowires (R-SiNWs), which have a disordered arrangement, for additional CHF improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 32 publications
(59 reference statements)
1
52
0
Order By: Relevance
“…In particular, it has been reported that aligned Si nanowire arrays can significantly enhance the critical heat flux compared to the random Si NWs in the case of pool boiling due to their higher wickability. 11 In this letter, we show that pattern Si nanowires can allow the shifting of the Leidenfrost temperature to higher values while maintaining a minimum droplet evaporation lifetime.…”
mentioning
confidence: 81%
“…In particular, it has been reported that aligned Si nanowire arrays can significantly enhance the critical heat flux compared to the random Si NWs in the case of pool boiling due to their higher wickability. 11 In this letter, we show that pattern Si nanowires can allow the shifting of the Leidenfrost temperature to higher values while maintaining a minimum droplet evaporation lifetime.…”
mentioning
confidence: 81%
“…The maximum reported HTC values on untreated surfaces are usually in the range of 20-60 kW m -2 K -1 . Using water as the working fluid, the CHF alone can be enhanced by coupling the hydrophilicity and micro/nanoroughness via nanowires or nanotubes [31,92,93], bio-templating [12], sintering [9,20,21], hierarchical structuring [42,94,95] or oxidation [28].…”
Section: Pool Boiling Enhancementmentioning
confidence: 99%
“…Studies have been carried out to enhance the CHF through surface modification at the microscale [4][5][6][7], nanoscale [8][9][10][11], and mixed micro/nanoscale [12][13][14]. Chu et al [4] reported an enhancement in the CHF on the surface of a micropillar array.…”
Section: Introductionmentioning
confidence: 99%